1985
DOI: 10.1083/jcb.100.5.1592
|View full text |Cite
|
Sign up to set email alerts
|

Identification of osteoclast-specific monoclonal antibodies.

Abstract: Studies on the origin, identification, and characterization of osteoclasts have been difficult. This is in part due to a lack of definitive osteoclast markers and the similarity of these cells in form and function to cells of the mononuclear phagocyte system. To solve this problem, we inoculated isolated chick osteoclasts into mice to generate osteoclast-specific monoclonal antibodies. Supernatants from growth-positive hybridomas were screened by indirect immunofluorescent methods against cultured osteoclasts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(33 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…The antibody to some extent outlines the cells, suggesting membrane-associated antigen (Fig. 1B, epifluorescence) as reported (18). Similarly, essentially all purified cells are tartrateresistant acid phosphatase-positive (Fig.…”
Section: Steroid and Calmodulin Effects On Avian Osteoclastmentioning
confidence: 59%
See 2 more Smart Citations
“…The antibody to some extent outlines the cells, suggesting membrane-associated antigen (Fig. 1B, epifluorescence) as reported (18). Similarly, essentially all purified cells are tartrateresistant acid phosphatase-positive (Fig.…”
Section: Steroid and Calmodulin Effects On Avian Osteoclastmentioning
confidence: 59%
“…Bone-attached cells were characterized by tartrate-resistant acid phosphatase staining and using a monoclonal antibody, 121F, reacting specifically with avian osteoclasts (Fig. 1), kindly supplied by Philip Osdoby, Washington University, Saint Louis, MO (18). Cells were fixed 2 h in 1% phosphate-buffered formalin at 4°C and incubated 30 min at 20°C with 121F antibody diluted 1:100 or an equivalent dilution of nonimmune ascites in phosphate-buffered saline with 0.05% polyoxyethylene sorbitan monooleate and 1% bovine serum albumin, washed, and incubated with fluoresceinated goat anti-mouse antibody (Sigma) at 1:500 dilution to identify bound primary antibody, washed, and examined by epifluorescence using 450 -490 nm excitation and a 520-nm barrier filter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, specific antibodies were raised against some osteoclast cell surface antigens, and immunohistochemical methods were proposed for osteoclast identification [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not specific, megakaryocytic lineage cells are TRAP Ϫ . Finally, previous studies have shown that the 121F mAb is specific for osteoclasts (23). Therefore, cells stained with the 121F mAb in bone-derived samples characterized by FCM can be considered to be human osteoclast-like cells due to their morphologic and cytochemical properties.…”
Section: Discussionmentioning
confidence: 99%